Antioxidant and Inhibition of Essential Oil of Siam Citrus Peel (Citrus Nobilis L.) Kintamani Test Against Candida albicans hat Caused Candidiasis Fungal Infection - Yunita, Hasnah; Wibawa, I Putu Agus Hendra; Phabiola, Trisna Agung (International Journal of Biosciences and Biotechnology; Vol 12 No 1 (2024): International Journal of Biosciences and Biotechnology, 2025)
Siam citrus (Citrus nobilis L.) is one of the annual fruit crops found across Indonesia. Kintamani siam citruses are common in the Kintamani sub-district due to their high productivity and easy cultivation. However, it thas been discovered that siam citrus peel contains several benefits such as antioxidants and antifungals. Antioxidants can preserve food quality as well as health and beauty by inhibiting oxidation reactions such as binding free radicals and highly reactive molecules, thereby preventing cell damage. Candidiasis is an infection that affects several body tissues such as in oral cavity, skin, and can also attack the vagina. Candida albicans is the fungus that causes candidiasis. This study aimed to determine the ability of siam citrus peel essential oil activity at reducing free radicals and the growth of Candida albicans. Hydro steam distillation was used to extract the essential oil of the citrus. The components of the compounds contained in the essential oil of siam citrus peel were identified using Gas Chromatography-Mass Spectrophotometry, the antioxidant activity of essential oil in reducing free radicals was tested using the DPPH 0.1 mM or 40 ppm method, and the inhibition of siam citrus peel essential oil was tested by agar well diffusion method. The results showed very low antioxidant activity with an IC50 in the amount of 55475.63 ppm. However, essential oil of siam citrus peel showed very strong inhibition against C. albicans at a concentration of 1% providing an inhibitory diameter of 21 mm in agar medium.